FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN PENGISIAN CATATAN MEDIS PADA PENERAPAN REKAM MEDIS ELEKTRONIK DI RSUD SULTAN SULAIMAN KAB SERDANG BERDAGAI TAHUN 2025 - Br Sinulingga, Emmenita Carina; Sari, Nur Mala; Dilla, Putri Salsa (Fakultas Kesehatan Masyarakat, Institut Kesehatan Deli Husada Deli Tua, 2025)
The implementation of electronic medical records (EMR) is an innovation in hospital service systems aimed at improving the efficiency and quality of healthcare services. However, the success of EMR implementation greatly depends on the compliance of health workers in accurately and completely filling out medical records. This study aims to analyze the factors associated with compliance in completing medical record documentation during EMR implementation at RSUD Sultan Sulaiman, Serdang Bedagai Regency, in 2025. This is a quantitative analytic study using a cross-sectional design. The research sample consisted of healthcare workers directly involved in EMR documentation. Data were collected using questionnaires and analyzed using the chi-square test. The results showed a significant relationship between human factors (man), machine factors, and material factors with compliance in EMR documentation. These findings suggest that the quality of human resources, readiness of technological infrastructure, and availability of supportive tools significantly influence the success of EMR implementation. Therefore, regular training, enhanced technological support, and strong managerial commitment are essential to improve compliance and the overall effectiveness of EMR systems in hospitals.